GAYA KEPEMIMPINAN BERDAMPAK TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN RITEL DI KOTA MAKASSAR - Maryani Maryani; Arifani Arifani (AkMen JURNAL ILMIAH, 2014)
The purpose of this study was to examine the impact of leadership style on the performance of retail companies in the city of Makassar, through the role of organizational culture that is responsive customer and knowledge management business competitiveness. The shape of this research is explanatory Researh performed in retail establishments of Modern Makassar. The sample was 375respondendari entire employee population numbering 2,312 people. Samples were taken by random sampling of each type of company and the type of work in retail establishments proportionally. Data were analyzed statistically through structural equation modeling (Structural Equation Model). The results showed that the impact of leadership style on performance improvement retailer directly and indirectly , through the role of organizational culture and knowledge management customer responsiveness and competitiveness of the retail company's business. However, knowledge management is not able to support the competitiveness of the business to increase the performance of retail companies in the city of Makassar.